ANALISIS PENGARUH PERTUMBUHAN EKONOMI DAN KEBIJAKAN DISTRIBUSI DALAM PERSPEKTIF EKONOMI ISLAM - Nopriyanto, Tri Wahyu; Setyanto, Alief Rakhman (STAI Darul Qalam Tangerang, 2024)
Economic growth is an increase in the value and amount of production of goods and services calculated by a country in a certain period of time based on several indicators, for example, an increase in national income, per capita income, a workforce that is greater than the number of unemployed, as well as a reduced poverty rate. Distribution is a marketing activity in order to facilitate the delivery of products from the hands of producers to consumers, while distribution policies are rules made within the scope of industry.